Kinetic prediction of reverse intersystem crossing in organic donor–acceptor molecules - Naoya Aizawa (Nature Portfolio, 2020)
Understanding and predicting the kinetics of reverse intersystem crossing (RISC) facilitates the design of materials. Here, the authors demonstrate a theoretical expression that reproduces experimental RISC rate constants ranging over five orders of magnitude in selected molecules.